Pathology, microbiology, and genetic diversity associated with Erysipelothrix rhusiopathiae and novel Erysipelothrix spp. infections in southern sea otters (Enhydra lutris nereis) - Chang, Ri K.; Miller, Melissa A.; Tekedar, Hasan C.; Rose, Divya; García, Julio C.; LaFrentz, Benjamin R.; Older, Caitlin E.; Waldbieser, Geoffrey C.; Pomaranski, Eric; Shahin, Khalid; Camus, Alvin C.; Batac, Francesca; et al. (Frontiers in Microbiology, 2024)
Erysipelothrix spp., including E. rhusiopathiae, are zoonotic bacterial pathogens that can cause morbidity and mortality in mammals, fish, reptiles, birds, and humans. The southern sea otter (SSO; Enhydra lutris nereis) is a federally-listed threatened species for which infectious disease is a major cause of mortality. We estimated the frequency of detection of these opportunistic pathogens in dead SSOs, described pathology associated with Erysipelothrix infections in SSOs, characterized the genetic diversity and antimicrobial susceptibility of SSO isolates, and evaluated the virulence of two novel Erysipelothrix isolates from SSOs using an in vivo fish model. From 1998 to 2021 Erysipelothrix spp. were isolated from six of >500 necropsied SSOs. Erysipelothrix spp. were isolated in pure culture from three cases, while the other three were mixed cultures. Bacterial septicemia was a primary or contributing cause of death in five of the six cases. Other pathology observed included suppurative lymphadenopathy, fibrinosuppurative arteritis with thrombosis and infarction, bilateral uveitis and endophthalmitis, hypopyon, petechia and ecchymoses, mucosal infarction, and suppurative meningoencephalitis and ventriculitis. Short to long slender Gram-positive or Gram-variable bacterial rods were identified within lesions, alone or with other opportunistic bacteria. All six SSO isolates had the spaA genotype–four isolates clustered with spaA E. rhusiopathiae strains from various terrestrial and marine animal hosts. Two isolates did not cluster with any known Erysipelothrix spp.; whole genome sequencing revealed a novel Erysipelothrix species and a novel E. rhusiopathiae subspecies. We propose the names Erysipelothrix enhydrae sp. nov. and Erysipelothrix rhusiopathiae ohloneorum ssp. nov. respectively. The type strains are E. enhydrae UCD-4322-04 and E. rhusiopathiae ohloneorum UCD-4724-06, respectively. Experimental injection of tiger barbs (Puntigrus tetrazona) resulted in infection and mortality from the two novel Erysipelothrix spp. Antimicrobial susceptibility testing of Erysipelothrix isolates from SSOs shows similar susceptibility profiles to isolates from other terrestrial and aquatic animals. This is the first description of the pathology, microbial characteristics, and genetic diversity of Erysipelothrix isolates recovered from diseased SSOs. Methods presented here can facilitate case recognition, aid characterization of Erysipelothrix isolates, and illustrate assessment of virulence using fish models.